Key to Holarctic species of Epitrix flea beetles (Coleoptera: Chrysomelidae: Galerucinae: Alticini) with review of their distribution, host plants and history of invasions - Bieńkowski, Andrzej O.; Orlova-Bienkowskaja, Marina J. (Zootaxa, 2016)
The genus Epitrix Foudras, 1860a has a worldwide distribution. Some species of Epitrix are major pests of potato, tomato, eggplant, tobacco and other plants in North America and Europe. Some pest species have been inadvertently introduced from North America to Europe, from Europe to North America and from both continents to some islands in Atlantic and Pacific oceans. Therefore, a key for the identification of all Holarctic species is necessary for plant quarantine and protection services. We have compiled the key for distinguishing Epitrix from genera that could be confused with it and a key for all Holarctic species of Epitrix with the figures of spermathecae and aedeagi and the checklist with a review of the geographical distribution, host plants and history of invasions. The following species are included: E. abeillei (Bauduer), E. allardii (Wollaston), E. atropae Foudras, E. brevis Schwarz, E. caucasica (Heikertinger), E. cucumeris (Harris), E. dieckmanni (Mohr), E. ermischi (Mohr), E. fasciata Blatchley, E. flavotestacea Horn, E. fuscula Crotch, E. hirtipennis (Melsheimer), E. humeralis Dury, E. intermedia Foudras, E. krali Döberl, E. lobata Crotch, E. muehlei Döberl, E. priesneri (Heikertinger), E. pubescens (Koch), E. ogloblini (Iablokov-Khnzorian), E. robusta Jacoby, E. setosella (Fairmaire), E. similaris Gentner, E. solani (Blatchley), E. subcrinita (LeConte), E. tuberis Gentner, E. warchalowskii (Mohr) and E. papa Orlova-Bienkowskaja.